Love at a Lighthouse : Libby's Lighthouse - Book 1 - Mathis, Susan G (Thorndike, Maine : Center Point Large Print, 2025)
"Elizabeth Montonna, daughter of the Tibbetts Point Lighthouse keeper, thought shed love the lighthouse life forever until her mother, on her deathbed, reveals a long- buried secret. Now Libbys world has been turned upside down, making her question if shell ever truly belong and be loved. But when a dashing young sailor appears on her shore, wounded and disoriented, she finds purpose in helping him recover. Although the man knows nothing about his past or identity, his kindness and character steal a little more of her heart each day. If only she knew his full name. When Owen awakes on the shore of Lake Ontario with no knowledge of who he is, or where he was headed when his ship wrecked, he has no choice but to accept the hospitality of the lighthouse keeper and his lovely daughter. But as Owen works to repay their kindness, and his relationship with Libby turns into something more, he knows their budding romance can go no further until he uncovers his past. With each passing day, Owen inches closer to discovering the secrets of his identity, but will the revelations bring him closer to Libby or tear them apart forever?"--
Keywords: Lighthouse keepers -- Fiction; Lighthouses -- New York (State); Fiction; Amnesiacs -- Fiction; Man-woman relationships -- Fiction; Family secrets -- Fiction; Thousand Islands (N.Y. and Ont.) -- History -- 19th century; Fiction; Christian fiction; Romance fiction; Historical fiction; Large print books